Peningkatan Pengetahuan dan Keterampilan bagi Kelompok Pemuda di Rasau Jaya Kubu Raya Melalui Edukasi Budidaya Jamur Tiram - Dwi Gusmalawati; Rafdinal Rafdinal; Rahmawati Rahmawati; Siti Khotimah; Surya Abi Alfariz; Lira Herlinda (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Oyster mushrooms are an agricultural product that has very promising prospects. The high nutritionalcontent and selling value of oyster mushrooms means that oyster mushroom cultivation needs to beimproved. Knowledge and skills about oyster mushroom cultivation need to be possessed so that thecultivation process can take place and produce optimal profits, especially for beginners. This educationalactivity was carried out to increase knowledge and skills regarding oyster mushroomcultivation for youth groups in Rasau Jaya Tiga, Rasau Jaya, Kubu Raya. The method of implementingthis educational activity is in the form of training with the delivery of theory and practice and evaluationby filling out a questionnaire. This oyster mushroom cultivation educational activity can increaseknowledge and skills for Rajati youth who initially did not know (81.82%) to know (54.55%) and are very knowledgeable (45.45%). This activity is 81.82% very useful and inspirational reaching 90.90%. Rajati youth hope that the results of this activity can be practiced or become an idea for creating a business in oyster mushroom cultivation both personally and in groups.